Referenciação : um estudo da anáfora encapsuladora em crônicas - Scarioti, Flávia (2014)
The present research is devoted to the investigation of the phenomenon of referentiation by occurred encapsulating anaphora in texts classified as chronic. The theoretical foundation that guides this work is divided into two chapters. The first chapter deals about the history of Textual Linguistics, with different approaches of text and textuality factors, constructed based on elaborations of Beaugrande and Dressler (1997), Koch (2009, 2011), Koch and Travaglia (2011), Bentes (2012), Fávero and Koch (2012), Marcuschi (1999, 2008, 2012) and Cavalcante (2010). The second chapter is dedicated to the referentiation, to the concept of anaphora and its classification, highlighting the case of encapsulation and is composed of the concepts presented by: Marcuschi (2000, 2001, 2008, 2010), Koch (2009, 2011), Cavalcante et al.(2010), Mondada and Dubois (2003), Apothéloz (2003), Koch and Elias (2008), Cavalcante (2003, 2010), Milner (2003), Conte (2003). So, we try to present a contextualization of Textual Linguistics, exposing the theoretical journey started in the 1960s and intended, effectively, in linguistic studies, in the 1970s, with the emergence of the concepts of interfrastics and referentiation mechanisms as textual resource. More specifically, the text proposes a study of anaphora, as textualization mechanism, presents the classification of this resource and its organization, especially the encapsulating anaphora. Considering the text as a communicative unit and recognizing textual genres, we present appraisals about the chronic textual genre as a way of human communication. Finally, we proceed to the textual analysis of three newspaper s chronic, based on the theory mentioned above, having as object of analysis the encapsulating anaphora. From the analysis, we observed that the anaphoric encapsulations are not only linguistic choices, but also the result of socio-cognitive context one the one who writes. We emphasize the importance of this resource in the textual organization and in the construction of meaning found in the chronicles